MANAJEMEN PEMBIAYAAN BANTUAN OPERASIONAL SEKOLAH PADA SMP NEGERI 4 BIREM BAYEUN DI KABUPATEN ACEH TIMUR. - Chairinda, Cut Zahri Harun, Nasir Usman. (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2016)
Abstract: the competence of the supervision of the head of the school is among the factors that influenced the increase in the professionalism of teachers. This research aims to describe: (1) the competence of the head of school in drawing up the programme of academic supervision to enhance the professionalism of teachers, (2) the principal kompetesi in implementing the program for academic supervision to enhance the professionalism of teachers, and (3) the competence of the head of school in following up on the results of academic supervision to enhance the professionalism of teachers. This research uses descriptive qualitative approach method. Data collection techniques used through observation, interviews, and documentation study. The subject of research is the principal, vice principal, teachers, and school superintendent. The results showed that: (1) the head of the SMA Negeri I Kuala Batee Southwest Aceh District have demonstrated a good supervision of competence, in particular in drawing up a program of academic supervision against the teacher. It can be seen from the supervision of the program has been compiled with set goals, objectives and implementation procedures of supervision, but less cooperation with the school superintendent. (2) the head of the SMA Negeri I Kuala Batee Southwest Aceh District have demonstrated a good supervision of competence, in particular in implementing the programme of academic supervision. It can be seen from the application of the models, approaches, and techniques of supervision that are run, but in the application of the techniques of observation has not been fitted with observation guidelines and (3) the competence of the supervision of the head of the SMA Negeri I Kuala Batee Southwest Aceh district in particular in follow-up on the results of supervision is still lacking. This can be from the follow-up results of supervision is performed by evaluating and providing feedback through individual talks with teachers who are disupervisi, but the principal did not devise an action plan next supervision.Keywords: Supervision, Competence, and professionalism of School Head Teachers.Abstrak: Pembiayaan pendidikan dana Bantuan Operasional Sekolah (BOS) di SMP Negeri 4 Birem Bayeun dilaksanakan melalui implementasi fungsi-fungsi manajemen yaitu perencanaan, pelaksanaan, dan pengawasan. Penelitian ini bertujuan untuk mengetahui perencanaan, penggunaan, pengawasan, serta faktor-faktor pendukung dan penghambat penggunaan biaya BOS pada SMP Negeri 4 Birem Bayeun di Kabupaten Aceh Timur. Pendekatan penelitian metode deskriptif. Teknik pengumpulan data dilakukan melalui wawancara, observasi, dan studi dokumentasi serta teknik analisis data yang digunakan meliputi kegiatan reduksi data, penyajian data, dan penarikan/verifikasi kesimpulan. Subjek penelitian Kepala Sekolah, Wakil Kepala Sekolah, guru, Komite Sekolah, Pengawas dan Konsultan dana BOS Dinas Pendidikan Kabupaten Aceh Timur. Hasil penelitian menunjukkan: (1) Perencanaan program dilakukan berdasarkan petunjuk teknis penggunaan dana BOS dengan melibatkan  guru, Komite Sekolah, dan Dinas Pendidikan serta melakukan sosialisasi kepada warga sekolah, orang tua serta masyarakat tentang program yang telah direncanakan, (2) Penggunaan dana BOS dilaksanakan sesuai dengan petunjuk teknis dan program yang telah direncanakan, (3) Pengawasan penggunaan dana BOS dilakukan oleh Komite Sekolah, dan Dinas Pendidikan. Pengawasan dilakukan dengan membandingkan antara program yang direncanakan dengan pelaksanaan., dan (4) faktor-faktor kekuatan penggunaan dana BOS adalah upaya mewujudkan visi dan misi, kepemimpinan kepala sekolah yang koperatif, tingkat pendidikan guru yang memadai, dukungan masyarakat akan kemajuan pendidikan, transparansi penggunaan dana BOS dan keinginan personil sekolah untuk meningkatkan mutu sekolah. Sedangkan faktor-faktor penghambat adalah kurangnya jumlah operator pendataan, anggaran yang diterima belum memenuhi semua kebutuhan sekolah, dan adanya pos-pos pembiayaan yang tidak tercantum dalam petunjuk teknis penggunaan dana BOS serta kurangnya partisipasi masyarakat dalam dukungan dana.Kata kunci: Manajemen, Pembiayaan, dan Bantuan Operasional Sekolah.